Dietary impact on canine behaviour - Harju, Camilla (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2016)
Currently there has been a lot of interest in nutritional effects on behaviour, but the connection between diet and behaviour is still quite unestablished in dogs. This literature review presents connections between nutrition, physiology and canine behaviour, and whether canine behaviour can be regulated by altering the diet, based on current scientific literature in this field. By altering the diet, availability of precursors for hormones and neurotransmitters that controls behaviour may be regulated. Activity level is found to be affected by the fermentability of dietary fibre, energy restriction and indirectly by energy surplus. Aggressive behaviour may be decreased by low protein content and tryptophan supplement. Undesirable behaviour caused by lack of satiety is affected by dietary fibre and their fermentability. Taken together, the studies presented in this review points towards that there is a connection between nutrition, physiology and behaviour in dogs, as well as that canine behaviour can be regulated to some extent by altering the diet. However, further research is required to draw more specific conclusion on how nutrition affect canine behaviour.